(untitled) - Ðào, Minh Trung (Cần Thơ, 2007)
This course is primarily concerned with the practical use of English speech, which consists of the following components: consonant clusters, linking sounds, word stress, sentence stress, and intonation. The course is based on British English accent and it is compiled from a variety of sourse of materials in relation to pronunciation, listening, and speaking.
Keywords: English language,English language; Phonetics,Pronunciation